The Impact of Pandemics on Workforce Joblessness in Central Europe in pre-Covid Era and during Pandemic - Michal Beno Beno (International Journal of Business and Social Science Research, 2021)
Unemployment affects individuals socially, personally, and economically. The impact of being jobless can be long-lasting. Five different generations participate in the workplace today. As countries throughout the world went into lockdown to combat the spread of Covid-19, unemployment numbers rose rapidly. This study aimed to examine the effects of unemployment in three-generation groups in V4 and Austria in the pre-Covid-19 era and during Covid-19. Descriptive statistics were used to present the collected data. OECD data were used for the analysis. Based on the data collected, unemployment decreases with age. The group aged 15-24 shows significantly higher unemployment than the other two groups. A gender difference in unemployment was confirmed only in the Czech Republic and Slovakia. Unemployment has increased during the Covid-19 pandemic. The unemployment gap for females before and during Covid-19 was not confirmed. The T-Test confirmed the difference in unemployment before and during the crisis in the age categories 15-24 and 25-54. In Hungary, Poland, and Slovakia, the number of people with a duration of employment of up to one year differs in all age categories. In the Czech Republic, there is a significant difference only between the youngest group and the other two. In all countries, the largest number of people with the employment of up to one year is in the age group 25-54. In none of the examined countries was a gender unemployment gap proved before Covid-19.